2018
DOI: 10.1111/ssqu.12520
|View full text |Cite
|
Sign up to set email alerts
|

On the Gender Gap in Financial Knowledge: Decomposing the Effects of Don't Know and Incorrect Responses*

Abstract: Objectives Past studies have consistently shown that women have lower levels of financial knowledge than men, and hence there is a noticeable gender gap in financial knowledge. We reconsider the conventional measures of financial knowledge by disentangling don't know (DK) responses and incorrect answers and comparing the effect of these two disparate responses’ on the gender gap in financial knowledge. Methods Using data from the 2012 National Financial Capability Studies data set, we estimate a series of ordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…However, there is an emerging strand of literature suggesting that gender differences in financial literacy scores may be attributable to measurement inaccuracy or may arise from distinct ways in which women and men respond to test questions. When accounted for different nature of incorrect and "Don't know" responses, financial literacy quizzes show a considerably smaller gender gap in test scores or the absence of a significant gender difference altogether (Bucher-Koenen, Alessie, Lusardi, & van Rooij, 2016;Z. Chen & Garand, 2018;Kim & Mountain, 2019;Ooi, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is an emerging strand of literature suggesting that gender differences in financial literacy scores may be attributable to measurement inaccuracy or may arise from distinct ways in which women and men respond to test questions. When accounted for different nature of incorrect and "Don't know" responses, financial literacy quizzes show a considerably smaller gender gap in test scores or the absence of a significant gender difference altogether (Bucher-Koenen, Alessie, Lusardi, & van Rooij, 2016;Z. Chen & Garand, 2018;Kim & Mountain, 2019;Ooi, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A greater inclination to select the "Don't know" response can also mask higher risk aversion of women (Z Chen & Garand, 2018;Lizotte & Sidman, 2009)…”
mentioning
confidence: 99%
“…In this study, debt knowledge was captured with a targeted instrument comprising 12 “Yes/No” questions. The option “Don't know” was intentionally omitted following the results of previous studies, which show a likely illusory gender gap in financial literacy resulting from (a) lower self‐confidence and (b) decreased inclination to make informed guesses among females (e.g., Chen & Garand, ; Lusardi & Mitchell, ). This decision was also supported by the conclusions of Krosnick and Presser () that “Don't know” filters—despite having some advantages—in general, do not improve measurement.…”
Section: Methodsmentioning
confidence: 99%
“…Some studies show, however, that the gap may be illusory, at least to a degree, as women tend to select the 'Don't know' option more often than men, ending up with worse financial literacy scores, because this option is routinely counted as indicating lack of knowledge. Men, instead, seem to gamble more frequently than women, and make an informed guess (Chen and Garand, 2018). Moreover, it was also found that women are less financially confident than men -they may know less than men, but they know more than they think they know .…”
Section: Discussionmentioning
confidence: 94%